The War in Ukraine and Migration to Poland: Outlook and Challenges - Maciej Duszczyk; Paweł Kaczmarczyk (Intereconomics, 2022)
The war initiated by Russia against Ukraine in February 2022 has resulted in the largest refugee migration in Europe since World War II, estimated by UNHCR (2022) at 6.3 million persons. In the first two months, almost 3.5 million war refugees crossed the Polish border, of which over 95% were Ukrainian citizens.
Keywords: F22; O15; R23; 330